Effects of a training program improve fitness in children soccer players (Impetus, 2021)
The purpose of this research work was to determine the effects on maximum cyclical speed (MCV), hamstring flexibility, explosive leg strength and maximum oxygen consumption (VO2Max.), Of a physical conditioning program based on the permanent use of the ball, in a group of infants belonging to a soccer school in the city of Armenia. A pre-experimental quantitative study with a pretest and posttest design without a control group, the population consisted of 20 male soccer players with 12.6 ± 0.5 years of age; To which the program designed by Patrice Marseillou was applied, which consisted of 30 sessions, with a frequency of 3 weekly sessions for 10 weeks. The results presented arithmetic differences between the pretest and posttest values ​​in the four study variables, 6.69 vs. 6.63 (m / s) for MCV; 7.70 vs. 6.95 (cm) in flexibility; 168.7 vs 171.05 (cm) in explosive strength; as of 46.7 vs. 48.7 (ml / kg-1 * min-1) in VO2Max, although these differences were not statistically significant (p> .05). In conclusion, the training program did not generate significant changes in the study variables, since although it has a playful component which is attractive to young people, it is not rigorous and structured enough with regard to frequency, intensity, duration, type of specific exercise, and gradual increase in loads as required to improve physical condition.